Spectrophotometric determination of acetaminophen and chlorzoxazone in tablets by multivariate calibration techniques - (:unkn) unknown (CHIMINFORM DATA S A, 2006)
Three multivariate techniques, Inverse Least Squares (ILS), Principal Component Regression (PCR) and Partial Least Squares (PLS) were applied to the spectrophotometric determination of acetaminophen (AC) and chlorzoxazone (CL) in tablets without prior separation. Stock solutions of acetaminophen and chlorzoxazone were prepared in methanol. Standard solutions were obtained by dilution of stocks with 0.1 M HCl. The multivariate calibrations were built up using training set containing both drugs in different concentration ratios and measuring the absorbances at 14 wavelengths with 5-nm intervals over the wavelength-range of 210-310 nm. Chemometric calculations were performed with MATLAB 7.0 software, The proposed techniques were applied to a commercial formulation, which contains 300 mg AC and 250 mg a(n=10). The results were statistically compared with each other, as well as those obtained by the developed HPLC method.
Keywords: multivariate spectral analysis; HPLC method; acetaminophen; chlorzoxazone; pharmaceutical tablet; SPECTRA DERIVATIVE SPECTROPHOTOMETRY; INVERSE LEAST-SQUARES; QUANTITATIVE-ANALYSIS; PSEUDOEPHEDRINE HYDROCHLORIDE; PHARMACEUTICAL FORMULATIONS; BENAZEPRIL HYDROCHLORIDE; LINEAR-REGRESSION; HYDROCHLOROTHIAZIDE; MIXTURE; PARACETAMOL